Clean coal technology on hot gas clean-up process with a moving granular bed filter. (15th July 2019) - Chen, Yi-Shun; Hsiau, Shu-San; Syu, Jhan-Ruei; Chang, Yi-Lun
Highlights: The irregular surface area of silica sand could improve the collection efficiency. The higher pressure drop could obtain the better of collection efficiency. The results of this study can be applied in industrial environments. Abstract: This study presents a filtration technology, aiming to increase the efficiency of industry environment under different integrations and acquire the optimum solution. The goal of this study is to evaluate the performance of a moving granular bed filter designed to filter out coal fly ash. A series of experiments were performed at room temperature to demonstrate the flow patterns of the moving granular bed filter under different operational parameters. The collection efficiency and the pressure drop were investigated under different filtration superficial velocities, mass flow rates of filter granules, and filter granules, but with a fixed inlet dust concentration. The results showed that, using a filtration superficial velocity of 20 cm/s and a mass flow rate of filter granules of 460 g/min, the outlet dust weight decreased and the amount of dust particulates deposited in the filter bed increased. Furthermore, the test results from this filtration method can be applied in different industrial applications with high-temperature environments.